Deformed steel fibres as minimum shear reinforcement — An investigation. (August 2016) - Jain, Kranti; Singh, Bhupinder
Abstract: An appraisal of crimped and hooked-end steel fibres as minimum shear reinforcement in reinforced concrete beams made with two concrete grades is presented. Beams conventionally detailed with minimum shear reinforcement were used as control specimens. The fibre reinforced beams also showed varying degrees of multiple cracking at peak loads. The shear strength of the fibre reinforced beams though lower than those of the conventionally detailed beams were higher than a lower bound value recommended in the literature as well as predictions from ACI 318. Effect of concrete grade on normalised shear strength was insignificant. Between the two deformed fibre types, depending upon the aspect ratio, the beams reinforced with the hooked-end fibres had up to 38% higher shear strengths than those containing the crimped fibres. The validity of the ACI 318 flexural performance criteria for deformed fibres proposed to be used as minimum shear reinforcement has been examined and a simple mechanics-based shear strength model for fibre reinforced concrete has been proposed. The proposed model together with seven shear strength models selected from the literature have been evaluated for their predictive efficacy.